Multi-level marketing strategies as a mechanism to achieve competitive superiority (exploratory research of the opinions of a sample of workers in the Al-Wareth factory for the production of refrigeration - Mahdi, Hawra Thamer; Kamel, Suhad Barqi; Hassan, Layla Mohsen (Eximia, 2023)
Through this research, the researchers sought to shed light on the concept of multi-level marketing, as it is an important and broad concept that applies to the approach of the factory in question, and to try to find out ways to follow its strategies in order to reach competitive superiority after shedding light on the latter. The researchers also endeavored to find out the extent of the impact of marketing strategies. Multi-level in achieving competitive superiority, as is the case to know the type of correlation between them. In order to achieve this, Al-Warith Factory for producing cooling devices was chosen as a field in order to test the research hypotheses through a questionnaire distributed to a sample of (100) workers in the factory. Through their research, the researchers reached many conclusions, the most important of which is (all multiple regression models were significant, which means that all strategies can be used to achieve competitive superiority, even to varying degrees) and among the most important recommendations that came out of the research (management’s attention and guidance to workers in order to consolidate the idea of multi-level marketing And adopting it as a main means of achieving competitive superiority.